Exploring the nature of stuttering through a behavioral-neuro-modulation intervention program in bilinguals with stuttering - Chanchal Chaudhary; Samir Kumar Praharaj; Gopee Krishnan (CoDAS)
ABSTRACT Purpose Investigations on identifying the nature of stuttering present varying views. The argument remains whether the stuttering dysfluencies have a motor or a linguistic foundation. Though stuttering is considered a speech-motor disorder, linguistic factors are increasingly reported to play a role in stuttering. Current literature points towards deficits in speech-related motor areas of the brain to abnormalities in linguistic planning and phonological memory playing a role in stuttering. Examining cross-linguistic generalization of treatment gains from treated to untreated language in bilinguals who stutter may provide a unique opportunity to explore the motor and linguistic factors in stuttering. Methods In the current study, we explored this potential by experimentally controlling the language of treatment in bilinguals with stuttering (BWS). We hypothesized that if the dysfluencies in stuttering arise from the underlying motor deficits, then the language of treatment would not play a significant role in cross-linguistic generalization. Sixteen BWS were given transcranial direct current stimulation (tDCS) along with behavioral intervention for three weeks. The language of treatment was randomized, wherein participants in one group received behavioral intervention in their dominant language and the other in their non-dominant language. Results Results showed that participants in both groups showed a reduction in their stuttering dysfluencies (% stuttered syllables) regardless of the language of treatment, and the treatment gains were generalized to the non-treated language. Conclusion Linguistic factors such as language dominance and structure of languages did not surface to play a role in the generalization, signaling the motoric nature of dysfluencies in stuttering.